Simo Lazarov and his timbral reading of „Sarabandе“ from „Classical and Romantic“ by Pancho Vladigerov - Becheva, Rositsa (Young Scientific Music and Dance Forum : Conference with international participation, 2021)
The topic focuses on Simo Lazarov`s electronic transcription of „Sarabande“ from „Classical and Romantic“ by Pancho Vladigerov, highlighting the peculiarities of this modern reading of the work. It analyses the ideas of sound design and the concept of timbral dramaturgy, the possibilities of timbre as a means of creating new associativity in relation to the sound canvas and the sound movement in the work, the capabilities of the orchestration – created by the means of electronic and computer music – for the interpolation of new musical imagery.